Enhancing Critical Thinking Through Augmented Reality-Based Nervous System E-Modules - Muhammad Nizar Maulana Nizar; Dadang Jaenudin; Irvan Permana; Indriyani Rachman; Toru Matsumono (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aims to develop an integrated nervous system e-module using Augmented Reality and to analyze its feasibility and effectiveness in improving the critical thinking skills of 11th-grade students. This study was primarily motivated by findings indicating deficiencies in students’ analytical reasoning skills in science, with a specific focus on biology. This study employed the Research and Development method using the ADDIE model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The study subjects consisted of 34 11th-grade students. The effectiveness test was conducted using a one-group pretest-posttest design. Critical thinking skills were measured using Ennis’s indicators. The research results show that the e-module developed met very high feasible criteria based on evaluations by experts and practitioners, including 1 media expert, 1 content expert, and 15 teachers. Calculation results show that the CVI score falls into the “very good” category. Achieving a score so close to perfection proves that the integration of Augmented Reality technology into the science module has been presented accurately, systematically, and in accordance with applicable language and graphic standards. The results of the e-module’s implementation proved effective in enhancing students’ critical thinking skills, as evidenced by an increase in the average score from the pretest to the posttest with an N-gain in the moderate category, where the greatest progress occurred in the “Advanced Clarification” and “Basic Support” indicators. The decrease in the standard deviation (SD) indicates that this e-module can reduce gaps in students’ understanding. Thus, this e-module is effective and suitable for use in enhancing students’ critical thinking skills.